Etnia e raça no desporto beirense da época colonial. O caso dos “sino-moçambicanos” - Eduardo Medeiros (Cadernos de Estudos Africanos)
From the beginning of the second half of the Twentieth century, sport started to develop as a significant form of recreation in Mozambique. The influence of neighbouring territories under British rule, the international contacts that residents of Beira and Lourenço Marques enjoyed, and the great facility with which sports were followed in the colonial capital led to a considerable rise in the practice of sports by the younger members of the so-called ”civilized population”, which included the Chinese. Thus, a veritable movement for the promotion of a sports culture developed, evidenced by the formation of clubs and associations. This paper begins by describing the history of the practice of sports and the evolution of sports institutions in the colonial society of Beira City, and goes on to describe the involvement of the Chinese community in federated and amateur sport.